Pengembangan Media Mosi ( Monopoli Puisi ) Materi Isi dan Amanat Puisi Kelas IV SDN Ngasemlemahbang - Linda Fibriya Hardiyanti; Rian Damariswara; Susi Damayanti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Background of this research is the teacher never uses learning media when teaching poetry material and often uses the lecture method so that learning is less interactive which causes students to be less skilled in writing and 60% of student learning outcomes under KKM. The purpose of this study is to describe the validity, practicality and effectiveness of MOSI media (Monopoly Poetry) on the content and message of poetry. This study uses the ADDIE model (R&D). The subjects of this study were 20 grade IV students at SDN Ngasemlemahbang. The results of this research indicate that the results of the validity of the Monopoly Poetry media (MOSI) obtain an average percentage of 83.5% with valid criteria. The results of the practicality of the Poetry Monopoly (MOSI) media obtained an average percentage of 92% with practical criteria. The results of the analysis of evaluation questions (post-test) obtained an average percentage of 82% with effective criteria. So it can be concluded that the MOSI (Poetry Monopoly) Content Material and Poetry Message for Class IV SDN Ngasemlemahbang which was developed was stated to be valid, practical, and effective.